Direct and Rapid Electrochemical Detection of Pseudomonas aeruginosa Quorum Signaling Molecules in Bacterial Cultures and Cystic Fibrosis Sputum Samples through Cationic Surfactant-Assisted Membrane Disruption - Buzid, A.; Reen, F.; Langsi, V.; Muimhneacháin, E.; O'Gara, Fergal; McGlacken, G.; Luong, J.; Glennon, J. (Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim, 2017)
Rapid detection of pathogenic bacteria present in patient samples is of utmost importance for the clinical management of bacterial-induced diseases. Herein, we describe an efficient and direct electrochemical approach for the detection of 2-heptyl-3-hydroxy-4-quinolone (PQS), 2-heptyl-4-hydroxyquinoline (HHQ), and pyocyanin (PYO) as a molecular signature of Pseudomonas aeruginosa (PA), a frequently infecting pathogen with high antibiotic resistance. The cationic surfactant hexadecyltrimethylammonium bromide (CTAB) enhances the effectiveness of an unmodified thin-film boron-doped diamond (BDD) electrode for the direct detection of PYO, HHQ, and PQS in bacterial cultures of PAO1 and PA14. Differential pulse voltammetry (DPV) is then used to monitor the production of these microbial metabolites in bacterial cultures of PAO1 over 10 h without any sample pretreatment. A proposed mechanism for the interaction of CTAB with bacteria cells is examined by zeta (?) potential measurements. Furthermore, the detection method is successfully extended to a clinical fluid matrix and applied to PA spiked cystic fibrosis (CF) sputum samples.